The Effects of Intact Cereal Grain Fibers, Including Wheat Bran on the Gut Microbiota Composition of Healthy Adults: A Systematic Review - Jefferson, Angie; Adolphus, Katie (Frontiers in Nutrition, 2019)
The human microbiota is increasingly recognized as a major factor influencing health and wellbeing, with potential benefits as diverse as improved immunity, reduced risk of obesity and Type 2 diabetes, and improved cognition and mood. Bacteria inhabiting the gut are dependent on the provision of fermentable dietary substrates making diet a major factor driving the composition of the human gut microbiota, and dietary fiber may modify microbiota abundance, diversity, and metabolism including short-chain fatty acid production. The majority of research to date has explored isolated fibers, and the influence of habitual fiber consumption has been less well established. The aim of the current article was to systematically review evidence from human intervention studies for the effects of intact cereal fibers and their active sub-fractions on gut microbiota composition in healthy adults. Studies published in the past 20 years were identified through the PubMed and Cochrane electronic databases. Inclusion criteria were: healthy adult participants (>18 years), inclusion of at least one intact cereal fiber, or its sub-fraction, and measurement of fecal microbiota related outcomes. As every individual has a unique microbiota many trials utilized a cross-over design where individuals acted as their own control. Outcome measures included change to the microbiota, species diversity, or species numbers, or metabolic indicators of microbiota fermentation such as short chain fatty acids or fecal nitrogen. 223 publications were identified and 42 included in the final review. In discussing the findings, particular attention has been paid to the effects of wheat fiber, bran and arabinoxylans (AXOS) as this is the dominant source of fiber in many Western countries. Thirty-nine of the forty-two studies demonstrated a positive impact of cereal fiber consumption on the gut microbiota, with effects apparent from 24 hours to 52 weeks. Increases in wheat fiber as low as 6-8g were sufficient to generate significant effects. Study duration ranged from 1 day to 12 weeks, with a single study over 1 year, and exploration of the stability of the microbiota following long-term dietary change is required. Increasing cereal fiber consumption should be encouraged to support a diverse and healthy microbiota and good overall health.